Heterotopic pregnancy. A case report - Adrianna Skrajna; Krzysztof Cendrowski; Habib Alkhalayla; Włodzimierz Sawicki (Journal of Ultrasonography, 2012)
Heterotopic pregnancy is the coexistence of living or dead intrauterine pregnancy, single or multiple, and extrauterine pregnancy located in the oviduct, ovary, uterine corner, cer‑ vix or peritoneal cavity. This condition is very rare (1:30 000 pregnancies). Nevertheless, in the latter years because of the development and accessibility of assisted reproductive techniques, the incidence of heterotopic pregnancies increased to 1:100 of pregnancies. The aim of this report is to present a case of early recognized intrauterine and extrauter‑ ine pregnancy. The case refers to 25‑year‑old patient, pregnant for the second time, in more or less 6th week of gestation, who had not been stated any heterotopic pregnancy incidence risk factors. After the observation lasting for several days in the Clinic, the pres‑ ence of a living intrauterine and coexisting extrauterine pregnancy located in the right oviduct was stated. The patient had her right oviduct removed by means of laparoscopy. After the surgery the patient with the living intrauterine pregnancy was released from the Clinic. Normal further course of intrauterine pregnancy. The patient gave birth around her expected delivery date. The presented case indicates the significance of correctly and carefully performed ultrasound examination. Moreover, it is a warning for the doctors performing ultrasound examinations in the early weeks of pregnancy – the visualization of a normal pregnancy in the ultrasound examination does not release the examiner from a necessity of precise imaging of adnexa of the uterus. Early diagnosis of this pathology, thanks to a precise ultrasound examination, decreases the risk of complication incidence as well as women mortality.